Promotion Strategy Of Batuan Integrated Tour Package “The Living Museum Of Batuan” In Increasing Revenue Of Batuan Tourism Village - I Gusti Putu Raja Darmadi; I Nyoman Sukma Arida; Irma Rahyuda (International Journal of Technology and Education Research, 2026)
Batuan Village in Gianyar Regency, Bali, is one of the cultural tourism destinations with significant potential to be developed through the Batuan Integrated Tour Package “The Living Museum of Batuan.” This study aims to analyze the promotional strategy of the Batuan Integrated Tour Package “The Living Museum” in increasing the income of Batuan Tourism Village. The research employed a quantitative descriptive approach, with data collected through questionnaires, observation, and documentation. The analytical tools used were Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), and SWOT analysis to formulate alternative promotional development strategies. The findings indicate that the total IFE score is 2.89, suggesting that the internal condition of the tourism village is relatively strong. The main strengths include unique cultural-based tourism experiences, direct interaction with local communities, and a positive image supported by online reviews and word of mouth. Meanwhile, the primary weaknesses are the suboptimal use of digital media, inconsistency in promotional content, and website management. The total EFE score of 3.21 shows that the tourism village is well-positioned to respond to external opportunities, particularly digital technology development, the growing trend of cultural and authentic tourism, and government support for tourism villages. However, threats include competition with other tourism villages, environmental issues, and risks related to policy changes and political fluctuations. Based on the SWOT analysis, SO, WO, ST, and WT strategies were formulated, focusing on strengthening digital promotion through cultural storytelling, developing eco-cultural tour packages, enhancing digital marketing capacity, differentiating the “Living Museum” concept, and establishing digital promotion standard operating procedures. These strategies are expected to improve competitiveness, expand the cultural tourism market, and sustainably increase the income of Batuan Tourism Village.